Neither winner books nor defeated books - Franganillo, Jorge (Anuario ThinkEPI, 2009)
Some alarming voices insist that ebooks will displace print books, even though electronic gadgets can´t surpass, or even equal, those qualities that make paper books ideal for prolonged reading. In the future, paper will still be a better material for some tasks, so it seems reasonable to think we will keep on using it.
Keywords: Print books; eBooks; Reading.